Decicion Making Sebagai Solusi Kekerasan Terhadap Anak Melalui Play Therapy - Diana, Nirva (Universitas Islam Negeri Raden Intan Lampung, 2017)
Decision-making (decision making) is one of the process of identifying problems and opportunities and then solving them. One of the most common problems in children is violence against children. Play therapy is a method of counseling in tackling violence against children. Playing is a natural medium for children to be able to tell and share their feelings. In a therapy session, the child who needs help in overcoming his emotional, behavioral, social and mental health problems and even violence will be released to express and channel his emotions in a way that he feels good and proper by using the game tools that are in the room in a safe situation And comfortable. Good decision-making is an important part of good management, because good decisions will determine good outcomes.